Energy Labelling and Ecodesign of solar thermal products: Opportunities, challenges and problematic implementation aspects. (February 2017) - Mathioulakis, Emmanouil; Babalis, Stamatis; Kalogirou, Soteris; Belessiotis, Vassilis
Abstract: This study discusses the consequences of recent European Regulations concerning the integration of water and/or space heating systems within the framework of the European Directives for Energy Labelling and Ecodesign. This development undoubtedly creates a completely new environment for the production and commercial distribution of solar thermal products, for the benefit of both producers and distributors of heating-energy handling appliances, as well as for the end users of those devices. This paper will first outline the requirements of the relevant regulations and highlight the critical parameters affecting the classification of products in energy classes. Specific failures, ambiguities and deficiencies related to the proposed procedures are indicated and discussed, noting that these factors can potentially undermine the objectivity, impartiality and effectiveness of the products' evaluation. It will conclude by proposing specific corrective measures which could be considered through the periodic revision anticipated in the Regulations. Highlights: Energy Labelling regulations create a new environment for solar thermal products. Ambiguities in the methodology can undermine the objectivity of product evaluation. Improvements in the technical background of the evaluation process are proposed.